Interfaith Tolerance in Tafsir Fath Al-Qadir and Tafsir of the Ministry of Religious Affairs of the Republic of Indonesia: Toleransi Antar Umat Beragama dalam Tafsir Fath Al-Qadīr dan Tafsir Kemenag RI (Takwil: Journal of Quran and Hadith Studies, 2023)
This article is based on the reality of life, especially Muslims in general, where there are still many Muslims who do not pay attention to religious tolerance in the life of the state and society. It can be seen from the reality that happened recently in Indonesia. The aim of this article is to look at the meaning and essence of tolerance in the Qur'an through the comprehension put forward by the tafsir experts by comparing the tafsir of Fath al-Qadir and the tafsir of the Ministry of Religious Affairs of Indonesia. The comparative method is carried out on the work of Imam Shaukani in the interpretation of Fath al-Qadir and the Qur'an and its Tafsir by the Ministry of Religious Affairs. This article finds that these two works of interpretation both emphasize that tolerance between religious communities only applies in the sociological aspect, not in the theological context. This argument was found through various verses in the Qur'an that talk about inter-religious relations, such as Q.S. Al-Baqarah: 256, Al-An'am: 108 and Al-Kafirun 1-6. In these verses, it is then illustrated that first, in the context of the da'wah passage there is no compulsion for non-Muslims to embrace Islam and it is strictly forbidden to hurt non-Muslims by mocking their God; second, there is no compromise for non-Muslims to invite to worship idols, because theological issues or monotheism are the identities and characteristics of a Muslim.